OPTIMIZATION OF PHYSICAL TRAINING AND TECHNICAL - TACTICAL IN THE LINE II A, LATCHES AND U18 AND U19 JUNIOR SHOOTER - Grosu Bogdan-Marius (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
Rugby, sports game characterized by constant contact game players in both defense and attack in the game, imposed a certain type of player that differs post they occupy within the team. This differentiation from all points of view (technical, tactical, psychological, somatic type) is all the more evident and more necessary as we advance along the value chain sportive.Specialitatea strict performance was imposed by the modern game as an objective necessity for achieving performance superioare.Ţinem to mention, however, that this specialization does not exclude but rather requires knowledge of basic technique and tactics of the game of rugby by individual player and athletic skills can be reached only through a deep specialization. This specialization makes the versatile player rugby player, is only possible following the "principles of modern game of rugby" technicality perfect value superior physical and tactical coordination deplină.Pornind from these considerations, the paper wanted to optimize and evaluate "qualities drawer, line II and lock in conditions of physical training and modern technical and tactical."